1987
DOI: 10.1159/000261029
|View full text |Cite
|
Sign up to set email alerts
|

An Anticaries Vaccine: Report on the Status of Research

Abstract: The state of the art of the research on a vaccine against dental caries has been reviewed. The subject has been analysed both from the biological and from the public health point of view. It is concluded that Streptococcus mutans plays a key role for the development of dental caries and that a vaccine directed against this microorganism could be a valuable adjunct to existing preventive measures in some countries. In others it could be a major public health measure. The unique characteristics of dental caries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 41 publications
(54 reference statements)
0
16
1
Order By: Relevance
“…IgG antibodies against SA I/II are reported to be protective against dental caries in immunized mon keys [Krasse et al, 1987] and in human adults with low caries experience [Challacombe et al, 1984]. We found no significant differences in total specific an tibodies between MS-positive and -negative groups.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…IgG antibodies against SA I/II are reported to be protective against dental caries in immunized mon keys [Krasse et al, 1987] and in human adults with low caries experience [Challacombe et al, 1984]. We found no significant differences in total specific an tibodies between MS-positive and -negative groups.…”
Section: Discussioncontrasting
confidence: 55%
“…The main source of infection is usually maternal saliva [Ber kowitz et ai., 1981;Berkowitz and Jones, 1985;Köhler and Bratthall, 1978;Masuda et ai., 1985] and high ma ternal salivary S. mutans levels (> 105cfu/ml) en hance its colonization [Berkowitz et al, 1981]. It has also been shown that the earlier the colonization by S. mutans, the more prone the children are to dental caries [Alaluusua and Renkonen, 1983;Köhler et al, 1988], Specific antibodies of secretory IgA isotype (in sal iva, milk or tears) and of IgG, IgM and IgA isotypes (in serum and crevicular fluid) against MS are found in most adults, but no consistent correlation between antibodies and caries prevalence among adults has been found [reviews in Brandtzaeg, 1983;Krasse et al, 1987], Also, studies on the possible association be tween antibodies and dental caries in children have proved equivocal [Tenovuo, 1986], In children, natu rally occurring salivary IgA antibodies seem to offer no protection against colonization of MS and/or against dental caries [Camling and Köhler, 1987;Ri viere and Papagiannoulis, 1987;Tenovuo et al, 1987;Aaltonen et al, 1988] whereas specific serum IgG an tibodies against S. mutans are often associated with low caries activity Aaltonen et al, 1987;Tenovuo et al, 1987]. Most of these analyses have been done using whole cells of S. mutans as anti gens which may lead to erroneous results because of possible cross-reactivity between various oral bacte ria, particularly streptococci [Bammann and Gib bons, 1979;Luo et al, 1988],…”
mentioning
confidence: 99%
“…The search for a caries vaccine, based on S. mutans antigens, has produced a large amount of valuable and interesting experimental data which have helped to develop understanding of the caries process and of immune responses in the mouth (Krasse et al, 1987;Russell and Johnson, 1987;Klein and Scholler, 1988). However, despite successful results in experimental animals, no human trials of active immunization with such vaccines have so far been reported.…”
Section: Dental Caries and The Streptococcus Mutans Groupmentioning
confidence: 99%
“…These antigens in clude glycosyltransferases and wall-associated proteins, such as antigen I/II (also known as antigen B and P|) and antigen A [Russell and Johnson. 1987;Krasse et al, 1987]. Antigen I/II has the advantage that it is found in all MS. but it has also been implicated in cross-reactions with human heart tissue.…”
Section: Vaccinationmentioning
confidence: 99%